Interpretability And Reliability In Neural Network-Based Paediatric Thyroid Nodule Diagnosis: A Framework For Clinical Integration - Khan A, Mohsin; Sharma, V K (Journal of Neonatal Surgery, 2025)
This research introduces TI-PedThyroNet (Transparent and Interpretable Paediatric Thyroid Network), a novel framework enhancing interpretability and reliability in neural network-based thyroid nodule diagnosis specifically for paediatric populations. By integrating complementary interpretability techniques with uncertainty quantification, the methodology addresses the critical trust gap in AI-driven paediatric diagnostics where radiation exposure concerns and long-term implications of interventions require particular attention. Our multi-pathway attention mechanism optimizes feature extraction while providing granular explanations. Clinical validation with paediatric radiologists demonstrates significant improvements in diagnostic confidence (31% increase), decision-making speed (34% reduction in interpretation time), and trust metrics. TI-PedThyroNet achieves state-of-the-art performance (accuracy: 92.8%, sensitivity: 94.3%, specificity: 91.6%) while providing human-interpretable explanations and reliable uncertainty estimates, demonstrating considerable potential for clinical integration in paediatric settings.